2019
DOI: 10.1111/dom.13687
|View full text |Cite
|
Sign up to set email alerts
|

Time trends in prescribing of type 2 diabetes drugs, glycaemic response and risk factors: A retrospective analysis of primary care data, 2010–2017

Abstract: Aim To describe population‐level time trends in prescribing patterns of type 2 diabetes therapy, and in short‐term clinical outcomes (glycated haemoglobin [HbA1c], weight, blood pressure, hypoglycaemia and treatment discontinuation) after initiating new therapy. Materials and methods We studied 81 532 people with type 2 diabetes initiating a first‐ to fourth‐line drug in primary care between 2010 and 2017 inclusive in United Kingdom electronic health records (Clinical P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
69
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 37 publications
6
69
1
Order By: Relevance
“…Based on the results of these key trials, the European Society of Cardiology and the European Association for the Study of Diabetes recommend SGLT2 inhibitors as first-line oral medication for specific T2DM patients, such as those with high-risk or established cardiovascular disease and chronic kidney disease [6]. Accordingly, the use of SGLT2 inhibitors has been rapidly increasing both globally [7], as well as in Japan [8].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results of these key trials, the European Society of Cardiology and the European Association for the Study of Diabetes recommend SGLT2 inhibitors as first-line oral medication for specific T2DM patients, such as those with high-risk or established cardiovascular disease and chronic kidney disease [6]. Accordingly, the use of SGLT2 inhibitors has been rapidly increasing both globally [7], as well as in Japan [8].…”
Section: Introductionmentioning
confidence: 99%
“…Sodium-glucose co-transporter-2 inhibitors (SGLT2i) are an increasingly important oral medication class in type 2 diabetes [1][2][3] with their use climbing dramatically in recent years. [4][5][6][7] They result in a broadly similar amount of glucose lowering compared with other oral agents but can also reduce blood pressure and result in modest weight loss. [8][9][10] In addition to their glucose lowering effects, large-scale clinical trials have demonstrated reduction in cardiovascular and renal outcomes in highrisk groups with type 2 diabetes, [11][12][13] as well as benefit in patients with heart failure whether or not they have type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, new evidences suggest that SGLT2 inhibitors and GLP-1 agonists have renoprotective effects [19]. And by 2017, SGLT2 inhibitors and GLP-1 agonists had comprised 17% and 11% of new firstto fourth-line prescriptions [20]. So, the prevalence of albuminuria may change in the next decade.…”
Section: Discussionmentioning
confidence: 99%